Lateral Extra-articular Tenodesis Reduces Failure of Hamstring Tendon Autograft Anterior Cruciate Ligament Reconstruction: 2-Year Outcomes From the STABILITY Study Randomized Clinical Trial. Issue 2 (February 2020) - Getgood, Alan M.J.; Bryant, Dianne M.; Litchfield, Robert; Heard, Mark; McCormack, Robert G.; Rezansoff, Alex; Peterson, Devin; Bardana, Davide; MacDonald, Peter B.; Verdonk, Peter C.M.; Spalding, Tim; ,; et al.
Background: Persistent anterolateral rotatory laxity after anterior cruciate ligament (ACL) reconstruction (ACLR) has been correlated with poor clinical outcomes and graft failure. Hypothesis: We hypothesized that a single-bundle, hamstring ACLR in combination with a lateral extra-articular tenodesis (LET) would reduce the risk of ACLR failure in young, active individuals. Study Design: Randomized controlled trial; Level of evidence, 1. Methods: This is a multicenter, prospective, randomized clinical trial comparing a single-bundle, hamstring tendon ACLR with or without LET performed using a strip of iliotibial band. Patients 25 years or younger with an ACL-deficient knee were included and also had to meet at least 2 of the following 3 criteria: (1) grade 2 pivot shift or greater, (2) a desire to return to high-risk/pivoting sports, (3) and generalized ligamentous laxity (GLL). The primary outcome was ACLR clinical failure, a composite measure of rotatory laxity or a graft rupture. Secondary outcome measures included the P4 pain scale, Marx Activity Rating Scale, Knee injury Osteoarthritis and Outcome Score (KOOS), International Knee Documentation Committee score, and ACL Quality of Life Questionnaire. Patients were reviewed at 3, 6, 12, and 24 months postoperatively. Results: A total of 618 patients (297 males; 48%) with a mean age of 18.9 years (range, 14-25 years) were randomized. A total of 436 (87.9%) patients presented preoperatively with high-grade rotatory laxity (grade 2 pivot shift or greater), and 215 (42.1%) were diagnosed as having GLL. There were 18 patients lost to follow-up and 11 who withdrew ( 5%). In the ACLR group, 120/298 (40%) patients sustained the primary outcome of clinical failure, compared with 72/291 (25%) in the ACLR+LET group (relative risk reduction [RRR], 0.38; 95% CI, 0.21-0.52; P < .0001). A total of 45 patients experienced graft rupture, 34/298 (11%) in the ACLR group compared with 11/291 (4%) in the ACL+LET group (RRR, 0.67; 95% CI, 0.36-0.83; P < .001). The number needed to treat with LET to prevent 1 patient from graft rupture was 14.3 over the first 2 postoperative years. At 3 months, patients in the ACLR group had less pain as measured by the P4 ( P = .003) and KOOS ( P = .007), with KOOS pain persisting in favor of the ACLR group to 6 months ( P = .02). No clinically important differences in patient-reported outcome measures were found between groups at other time points. The level of sports activity was similar between groups at 2 years after surgery, as measured by the Marx Activity Rating Scale ( P = .11). Conclusion: The addition of LET to a single-bundle hamstring tendon autograft ACLR in young patients at high risk of failure results in a statistically significant, clinically relevant reduction in graft rupture and persistent rotatory laxity at 2 years after surgery. Registration: NCT02018354 (ClinicalTrials.gov identifier)